Usage Of Asp.Net Ajax for Binus School Serpong Web Applications - Iskandar, Karto; Putranto, Andrew Thejo (ComTech: Computer, Mathematics and Engineering Applications, 2016)
Today web applications have become a necessity and many companies use them as a communication tool to keep in touch with their customers. The usage of Web Application in current time increases as the numberof internet users has been rised. For reason of Rich Internet Application, the desktop application developer wasmoved to web application developer with AJAX technology. BINUS School Serpong is a Cambridge Curriculum base International School that uses web application for access every information about the school. By usingAJAX, performance of web application should be improved and the bandwidth usage is decreased. Problems thatoccur at BINUS School Serpong is not all part of the web application that uses AJAX. This paper introducesusage of AJAX in ASP.NET with C# programming language in web application BINUS School Serpong. It is expected by using ASP.NET AJAX, BINUS School Serpong website performance will be faster because of reducing web page reload. The methodology used in this paper is literature study. Results from this study are to prove that the ASP.NET AJAX can be used easily and improve BINUS School Serpong website performance. Conclusion of this paper is the implementation of ASP.NET AJAX improves performance of web application in BINUS School Serpong.